EFFECT OF HIGH PRESSURE COOLANT JET (HPCJ) IN DRILLING AISI 4340 STEEL - P.SATYANARAYANA; B.ANITHA; YALAGANDALA AKSHAY KUMAR (International Journal of Innovations in Engineering Research and Technology, 2021)
High production machining, grinding and drilling inherently generates large amount of heat leads to high cutting zone temperature for its higher cutting velocity, feed and depth of cut, Such high cutting temperature if not reduced impairs surface integrity of the product and reduce the dimensional accuracy as well as tool life. Applications of cutting fluids change the performance of machining operations because of their lubrication, cooling, and chip flushing functions. However, the conventional cutting fluids are not thateffective in such high production drilling. Low boiling temperature cause vaporization of cutting fluid and prevent it to enter into the cutting interface making a barrier to flow. In addition, flowing chips through drill flute prevent the fluid to enter into the cutting zone. Further, they also deteriorate the working environment and lead to general environmental pollution.High-pressure coolant presents itself as a viable alternative for drilling with respect to heat dissipation, roundness deviation and taper of the hole, chip formation mode and tool wear. This study compares the mechanical performance of high-pressure coolant to completely dry lubrication for the drilling of AISI-4340 steel based on experimental measurement of roundness deviation, surface roughness, chip formation mode and tool wear, Results indicated that the use of high-pressure coolant leads to lower roundness deviation and surface roughness, favorable chip-tool interaction and reduced tool wear